2009
DOI: 10.1097/01.pra.0000344917.43780.77
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence: A Review of the Literature and Implications for Clinical Practice

Abstract: Adherence is defined as the extent to which a patient's behavior coincides with medical or prescribed health advice. Adherence is considered non-judgmental and is preferred over the term "compliance," which carries negative connotations and suggests blame for the patient. A major challenge in the field of psychiatry has been to understand why patients may or may not adhere to medication and other treatment recommendations. A comprehensive review of the literature on medication adherence among patients with psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
196
0
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(217 citation statements)
references
References 64 publications
7
196
0
14
Order By: Relevance
“…Adherence was measured using a single self-report item summarizing adherence to physician recommendations over 2 years, rather than more objective and specific measures of the many dimensions of adherence that may occur in the management of sickle cell disease. While patient self-report is widely used in studies of adherence due to its simplicity, inexpensive nature, and known clinical utility, 7,29,30 it has also been known to lead to overestimates of adherence. One study found that patients overestimated their level of adherence to antihypertensive medications by an average of 17 %.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence was measured using a single self-report item summarizing adherence to physician recommendations over 2 years, rather than more objective and specific measures of the many dimensions of adherence that may occur in the management of sickle cell disease. While patient self-report is widely used in studies of adherence due to its simplicity, inexpensive nature, and known clinical utility, 7,29,30 it has also been known to lead to overestimates of adherence. One study found that patients overestimated their level of adherence to antihypertensive medications by an average of 17 %.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, studies show that medication adherence is suboptimal, with rates ranging from 20% to 70%. 6,7 As medication experts, pharmacists can play a key role in assisting patients with medicationrelated education and therapy management, especially medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…How would you rate how things were in today's session overall? 1 We slightly modified the Approach question on the SRS to reflect the clinical context of community pharmacy rather than behavioral health; thus, the Approach question was reworded to refer to a "pharmacist's" approach rather than a "therapist's" approach.…”
Section: The Smarta Projectmentioning
confidence: 99%
“…1 Patient medication adherence, or taking medications as prescribed, is considered to be a significant clinical issue. 2 The Study of Medication Adherence and the Therapeutic Alliance (SMARTA), an industry-sponsored study conducted by University of Pittsburgh School of Pharmacy, was a project intended to assess the relationship between the administration of two scales and medication adherence.…”
Section: Introductionmentioning
confidence: 99%